2011
DOI: 10.1111/j.1365-2362.2011.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis is associated with adiponectin resistance in chronic hepatitis C virus infection

Abstract: In patients with chronic HCV hepatitis, fibrosis was associated with hyperadiponectinemia. Chronic HCV-infected hepatocytes showed reduced ADIPOR1 expression, suggesting a pattern of adiponectin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
(46 reference statements)
2
25
2
Order By: Relevance
“…The major driving force for decreasing adiponectin after SVR was thus directed to, at least partly, attenuated hepatic fibrosis in many aspects. However, the current study did not support the connection between adiponectin alterations and adiponectin resistance, 19 as IHC studies failed to demonstrated a significant difference in hepatic adiponectin receptor expression between CHC patients and the controls. In addition, after SVR, the HCV-associated hypolipidemia was reversed (Table S2).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The major driving force for decreasing adiponectin after SVR was thus directed to, at least partly, attenuated hepatic fibrosis in many aspects. However, the current study did not support the connection between adiponectin alterations and adiponectin resistance, 19 as IHC studies failed to demonstrated a significant difference in hepatic adiponectin receptor expression between CHC patients and the controls. In addition, after SVR, the HCV-associated hypolipidemia was reversed (Table S2).…”
Section: Discussioncontrasting
confidence: 94%
“…[14][15][16] Because both HCV infection and adiponectin are critically involved in metabolism, their precise relationship might aid to probe the therapeutic targets for HCV-associated cardiometabolic complications but remains inconclusive. For example, compared with controls, serum adiponectin levels have been reported to be higher, [17][18][19] lower 20 or not different 21 in chronic hepatitis C (CHC) patients. All studies 17,[22][23] but one 24 failed to correlate HCV viral load with adiponectin levels.…”
Section: Introductionmentioning
confidence: 99%
“…[43, 44] Cirrhosis is thought to lead to a state of adiponectin resistance, with downregulation of adiponectin receptors in liver tissue and decreased clearance of adiponectin. [4548]. However, we did not find a statistically significant association between liver fibrosis and peripheral adiponectin levels.…”
Section: Discussioncontrasting
confidence: 73%
“…F>=2) are both independently associated with SVR rather than OPN simply acting as a surrogate marker of fibrosis. These findings in relation to virologic response have to be interpreted with caution given the limited size of our study cohort and absence of IL28B data for these patients that received peg-IFN and RBV prior to availability of IL28B genotyping assays (34, 35). Levels of serum adiponectin have been reported to correlate with HCV-fibrosis stage (35).…”
Section: Discussionmentioning
confidence: 92%
“…These findings in relation to virologic response have to be interpreted with caution given the limited size of our study cohort and absence of IL28B data for these patients that received peg-IFN and RBV prior to availability of IL28B genotyping assays (34, 35). Levels of serum adiponectin have been reported to correlate with HCV-fibrosis stage (35). Although we noted a positive correlation between serum OPN and adiponectin (p=0.042), serum adiponectin was not found to be independently associated with either fibrosis stage or SVR.…”
Section: Discussionmentioning
confidence: 92%